DINAMIKA PEMBAHARUAN HUKUM KELUARGA ISLAM DI INDONESIA - Setiawan, Eko (De Jure: Jurnal Hukum dan Syari'ah, 2014)
This article will elaborate the thought of renewing of Islamic family law in Indonesia. Family law generally is the law based on family ties. This family ties can occur because of consanguinity, or occur because of a marriage. The family relationships are very important because there is nothing to do with the relationship to the children and the parents, the law of inheritance, custody and guardianship. Basically source of family law can be divided into two kinds, namely the source of written and unwritten laws. Written source of family law is a source of law derived from a variety of legislation, jurisprudence, and treaties. While the source of the unwritten law is a source of law that grows and develops in society lifes.